The existential mode of death in the collection «Blockpost» by Borys Humeniuk - Матвієнко, Валерія (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article is devoted to investigation of the existential mode of death in B. Humeniuk’s Blokpost collection. The place of creativity of the writer among other works about war in modern Ukrainian literature is investigated. The focus is on traditional images and mythologems, which the writer are rethinking, giving them new shades of meaning. The mode of death in the writer’s creative work is interpreted by the specificity of the image of temporal-spatial unity, in particular the text traces a linear time stream, which reflects the forms of past memory, the category of eternity and the specifics of national memory in the life after the war. It is revealed that in most of the poems of the Blokpost collection there is a change of locus (crossing the threshold of the house, transition from the world of the living to the world of the dead). The modus of death is explored through the philosophical categories of existentialism, as the heroes of B. Humeniuk’s works are found themselves every time in boundary situations that change the perception of life and death. The writer is characterized by an ontological perception of death, which is projected into the system of everyday priorities of the characters. It is determined that death is only a link in the cycle of being, since it is always life-changing. Therefore, the creativity of the writer is characterized by a life-affirming pathos, which speaks of the humanistic direction of the text. Much attention is focused on the attitude of heroes and narrators to death, in particular death acquires the following antinomic features: sacrificial death and senseless death.